Exercise and its relation to students' working memory- a preliminary study / Wan Noor Ainun Baharuddin and Syukriah Najaa Mohd Khalid - Baharuddin, Wan Noor Ainun; Mohd Khalid, Syukriah Najaa (Universiti Teknologi MARA Cawangan Pahang, 2020)
The practice of cardiovascular exercise triggers a cascade of neurobiological mechanisms that enhance human memory processing. The objective of this study was to understand the relationship of acute, moderate-intensity exercise to working memory (WM) performance by using N-back task as a performance measure. In a within-participants design, students from second semester Diploma, Faculty of Sport Science, Universiti Teknologi MARA, Pahang aged between 19 to 24 years old, females (n = 31) performed a N-back task: 1) a rest-cognition intervention, in which they performed a cognitive task without exercising; 2) an exercise-cognition intervention, in which they performed a cognitive task 5-minutes immediately after the task. 8 subjects had increment in N-back load compared to before exercise session and 9 subjects had similar N-back load performance. However, 7 subjects had decrement in performance. The exercise-only intervention resulted in an increment pattern of hit rate and decreased reaction times, suggesting that simple aerobic exercise had a beneficial impact on working memory. However, for memory reaction time (p=0.515) and accuracy (p=0.216), both did not show significant differences. A few subjects had decreased in performance which is indicative of cognitive fatigue caused by the additional cognitive demands. In summary, our findings suggest that acute, moderate-intensity exercise differentially influence the subject's performance. Subjects can maintain and improve the N-back level, gives some initial indication that this activity may help to improve students' WM cognition. While the decrement in performance among other 8 subjects may be caused by cognitive fatigue may interfere the beneficial post-exercise outcomes.